Interface and composition engineering of vanadium doped cobalt nickel sulfide/phosphide heterostructure for efficient water splitting. (1st February 2021) - Suo, Na; Dou, Zhiyu; Cui, Lili
Highlights: The ECSA is increased through producing heterogeneous interfaces. The electron state of Ni, Co is modulated by introducing V and generating interfaces. The V-CNS/P/NF only requires an overpotential of 38 mV at 10 mA cm −2 for HER. Abstract: Developing efficient and robust non-noble electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is desirable for future green energy systems of electrochemical water splitting technology. Thus, the vanadium doped cobalt nickel sulfide/phosphide heterostructure catalyst supported on nickel foam (V-CNS/P/NF) is fabricated by sulfidation reaction, followed by phosphorization from the layer double hydroxide (LDH) precursor. After V doping, the peak position of Ni and Co shifts negatively. Simultaneously, it is noted that the introduction of V into CNS/P can result in the enhanced electrochemical surface area and improved conductivity of CNS/P. Importantly, the optimal electrocatalyst of V-CNS/P/N exhibits excellent performance in alkaline condition with small overpotentials of 38 mV and 210 mV to achieve 10 mA cm −2 for HER and OER, respectively. Remarkably, V-CNS/P/NF needs lower overpotential than that of Pt/C to reach higher current density of 500 mA cm −2 . A two-electrode system both assembled by as-prepared V-CNS/P/NF for electrochemical water splitting requires a cell voltage of 1.56 V to reach 10 mA cm −2 .